Assessment of treatment response in cardiac sarcoidosis based on myocardial 18F-FDG uptake - Frischknecht, Lukas; Schaab, Jan; Schmauch, Eloi; Yalamanoglu, Ayla; Arnold, Dennis D.; Schwaiger, Judith; Gruner, Christiane; Buechel, Ronny R.; Franzen, Daniel P.; Kolios, Antonios G.A.; Nilsson, Jakob (Frontiers in Immunology, 2023)
Objective: Immunosuppressive therapy of cardiac sarcoidosis (CS) still largely consists of corticosteroid monotherapy. However, high relapse rates after tapering and insufficient efficacy is a significant problem. The objective of this study was to investigate the efficacy and safety of non-biological and biological DMARDs (nb/bDMARDs) considering control of myocardial inflammation assessed by 18-F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) of the heart.Methods: We conducted a retrospective analysis of treatment response to nb/bDMARDs of all CS patients seen in the sarcoidosis center of the University Hospital Zurich between January 2016 and December 2020.We identified 50 patients with CS. Forty-five patients with at least one follow-up PET-CT scan were followed for a mean of 20.5±12.8 months. Most of the patients were treated with prednisone and concomitant nb/bDMARDs. At first follow-up PET/CT scan after about 6.7±3 months, only adalimumab showed a significant reduction in cardiac metabolic activity. Furthermore, comparing all serial follow-up PET-CT scans (143) TNF inhibitor (TNFi) based therapies showed a statistically significant better suppression of myocardial 18F-FDG uptake compared to other treatment regimens. On last follow-up, most adalimumab-treated patients were inactive (n=15, 48%) or remitting (n=11, 35%) and only 5 patients (16%) were progressive. TNFi was safe even in patients with severely reduced left ventricular ejection fraction (LVEF) and a significant improvement of LVEF under TNFi treatment was observed.Conclusions: TNFi show better control of myocardial inflammation compared to nbDMARDs and corticosteroid monotherapies in patients with CS. TNFi was efficient and safe even in patients with severely reduced LVEF.